Investigating growth spillovers from Europe - Kalra, Sanjay (IMF Working Papers; Working Paper ;, 2010)
The paper characterizes trade exposure and regional integration in six ASEAN economies during 1997-2008. For this, the paper uses the 2000 Asian Input Output Tables which are extrapolated using National Income Accounts and COMTRADE data. On the demand side, the paper shows that the level and geographical nature of external exposure varies across the ASEANs, and has changed over time. In particular, there was a shift in the external demand exposure of ASEANs from mature markets, including the United States, to China and ROW. In addition, the share of China in East Asia's final demand, especially investment, rose sharply while that of Japan fell. On the supply side, the paper documents the rise of China into a 'global factory' and the steady shift in regional production and integration from Japan and the United States to China.